PROGRAM PENGABDIAN MAHASISWA: ASISTENSI MENGAJAR DI UPT SDN 064024 MEDAN SELAYANG TAHUN AJARAN 2024/2025 - Simarmata, Ester Julinda; Sitepu, Anton; Gulo, Willfrida Purnama Sari; Kudadiri, Efani; Simanullang, Wenny Febriani; Sitepu, Asril Kisbat; Br. Sinulingga, Ateta Malem; Sitio, Sahmaita (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
The Teaching Assistance Program is part of the implementation of the Higher Education Curriculum aimed at improving students’ pedagogical, professional, social, and personal competencies as future teachers. This activity was carried out by students of the Primary School Teacher Education Study Program at Universitas Katolik Santo Thomas during the even semester of the 2024/2025 academic year at UPT SDN 064024 Medan Selayang. The implementation method was collaborative and practice-based, involving classroom observation, lesson planning and delivery, learning assistance, as well as participation in non-teaching and extracurricular activities. The results of the program indicate that students were able to effectively integrate learning theories with real-world classroom practices. Furthermore, their involvement in various school activities contributed to strengthening their professional character as future educators. This program has proven to be a holistic and contextual learning platform to prepare students for careers in primary education.